Anthropometric study of nasal index in Hausa ethnic population of northwestern Nigeria - Ibrahim Mohammed; Tahmineh Mokhtari; Sahar Ijaz; Akanji Omotosho D; Abdullahi Abubakar Ngaski; Maryam Milanifard; Gholamreza Hassanzadeh (Journal of Contemporary Medical Sciences, 2018)
Objective Anthropometric study is very important in differentiating a true race from the local mingling of races. The nasal index has a great value in anthropological studies, because it is one of the anthropometric indices acknowledged in nasal surgery as well as management. Anthropometric studies are very important area for craniofacial surgery and syndromology. This study aimed to provide baseline data of nasal index of northern Nigerian people and to classify their nose type and the comparison of the data with other studies. Methods The nasal width and height were measured from 200 participants of Hausa ethnic group of northwestern Nigeria, nasal index (NI) was calculated and analyzed statistically. Results There was a significant difference in the nasal width (P = 0.0001), height (P = 0.0001) and NI (P = 0.0001) of sex groups, with nasal shapes: 120 mesorrhine (60%), 75 leptorrhine (37.5%) and 5 platyrrhine (2.55%). It shows Hausa people have a mesorrhine nose. Conclusion The nasal index of males is higher than females; this study presents the data for Hausa people in this area, which will be of  clinical, surgical interest in Rhinology. We recommend a further study to compare the nasal index of Hausa and other ethnic group living in northwestern Nigeria.